Contemporary approach to diagnostics in women with suspected pelvic endometriosis: Sodoben pristop k diagnostiki žensk s sumom na pelvično endometriozo - Knez, Jure; Dovnik, Andraž; Pakiž, Maja; But, Igor; Reljič, Milan; Gavrić Lovrec, Vida; Banović, Maja; Takač, Iztok (Acta Medico-Biotechnica, 2021)
Endometriosis is a common chronic female reproductive system disease, characterised by the presence of endometrial tissue outside the endometrium and myometrium. It can severely compromise quality of life and have an impact on fertility. Although advances in conservative medical treatment options have been made, surgery is often a necessary part of treatment for this insidious disease. Historically, it was believed that only ovarian endometriosis could be diagnosed non-invasively by an ultrasound examination, while endometriosis at other locations could not be observed. With advances in imaging techniques over the last decades, this has changed dramatically and today deep pelvic endometriosis can be diagnosed non-invasively with high sensitivity and specificity. The aim of this review is to evaluate the contribution of clinical examination, laparoscopy, and non-invasive imaging techniques, mainly transvaginal ultrasound and magnetic resonance imaging, to diagnose deep pelvic endometriosis. Evidence shows that transvaginal ultrasound with high-quality equipment in experienced hands offers high diagnostic accuracy for deep pelvic endometriosis diagnosis. Comprehensive ultrasound examination should be used as a first-line method of choice in diagnostics of women with suspected endometriosis and chronic pelvic pain.